Mapping the laminin receptor binding domains of Neisseria meningitidis PorA and Haemophilus influenzae OmpP2 - Abouseada, Noha M.; Assafi, Mahde Saleh A.; Mahdavi, Jafar; Oldfield, Neil J.; Wheldon, Lee M.; Wooldridge, Karl G.; Ala'Aldeen, Dlawer A.A. (Public Library of Science, 2012)
Neisseria meningitidis, Haemophilus influenzae and Streptococcus pneumoniae are major bacterial agents of meningitis. They each bind the 37/67-kDa laminin receptor (LamR) via the surface protein adhesins: meningococcal PilQ and PorA, H. influenzae OmpP2 and pneumococcal CbpA. We have previously reported that a surface-exposed loop of the R2 domain of CbpA mediates LamR-binding. Here we have identified the LamR-binding regions of PorA and OmpP2. Using truncated recombinant proteins we show that binding is dependent on amino acids 171–240 and 91–99 of PorA and OmpP2, respectively, which are predicted to localize to the fourth and second surface-exposed loops, respectively, of these proteins. Synthetic peptides corresponding to the loops bound LamR and could block LamR-binding to bacterial ligands in a dose dependant manner. Meningococci expressing PorA lacking the apex of loop 4 and H. influenzae expressing OmpP2 lacking the apex of loop 2 showed significantly reduced LamR binding. Since both loops are hyper-variable, our data may suggest a molecular basis for the range of LamR-binding capabilities previously reported among different meningococcal and H. influenzae strains.